Menstrual blood-derived mesenchymal stem cells differentiate into functional hepatocyte-like cells - Mou, Xiao-zhou; Lin, Jian; Chen, Jin-yang; Li, Yi-fei; Wu, Xiao-xing; Xiang, Bing-yu; Li, Cai-yun; Ma, Ju-ming; Xiang, Charlie (Journal of Zhejiang University. B. Science, 2013)
Orthotopic liver transplantation （OLT） is the only proven effective treatment for both end-stage and me- tabolic liver diseases. Hepatocyte transplantation is a promising alternative for OLT, but the lack of available donor livers has hampered its clinical application. Hepatocyte-like cells （HLCs） differentiated from many multi-potential stem cells can help repair damaged liver tissue. Yet almost suitable cells currently identified for human use are difficult to harvest and involve invasive procedures. Recently, a novel mesenchymal stem cell derived from human menstrual blood （MenSC） has been discovered and obtained easily and repeatedly. In this study, we examined whether the MenSCs are able to differentiate into functional HLCs in vitro. After three weeks of incubation in hepatogenic diffe- rentiation medium containing hepatocyte growth factor （HGF）, fibroblast growth factor-4 （FGF-4）, and oncostain M （OSM）, cuboidal HLCs were observed, and cells also expressed hepatocyte-specific marker genes including albumin （ALB）, a-fetoprotein （AFP）, cytokeratin 18/19 （CK18/19）, and cytochrome P450 1A1/3A4 （CYPIAI/3A4）. Differen- tiated cells further demonstrated in vitro mature hepatocyte functions such as urea synthesis, glycogen storage, and indocyanine green （ICG） uptake. After intrasplenic transplantation into mice with 2/3 partial hepatectomy, the MenSC-derived HLCs were detected in recipient livers and expressed human ALB protein. We also showed that MenSC-derived HLC transplantation could restore the serum ALB level and significantly suppressed transaminase activity of liver injury animals. In conclusion, MenSCs may serve as an ideal, easily accessible source of material for tissue engineering and cell therapy of liver tissues.